A calibration method of dual two-dimensional laser range finders for mobile manipulator. (23rd September 2019) - Song, Tao; Wei, Bang-Guo; Guo, Shuai; Peng, Jiang-Tao; Han, Dong-Xiao
In this article, a method for calibrating the relative position between dual two-dimensional laser range finders is proposed. This relative position is affected by the manufacture or assembling error of mobile platform, and this error could reduce the accuracy of localization. This article focuses on three-degree-of-freedom calibration, that is, one rotational and two translational degrees of freedom. The entire calibration process can be summed up into three steps. The first step is to allow the dual finders to scan one corner at the same time and then extract the parameters of the corner. The second step is to establish a cost function which is established according to the direction vector of the line and the repeatability of the corners. With this function, the genetic algorithm is used to obtain the final calibration result. Moreover, the finder systematic error and the statistical error are also considered into this article. Simulations and experiments are carried out to verify the proposed method.